An Integrated English Model to Enhance English Competence in Islamic Higher Education through Habituation and Language Environment - Darmayenti Darmayenti; Renggi Vrika; Chanti Diananseri; Salsabilla Gustia (AT-TA'LIM, 2024)
The aim of this study was to develop an integrated model for enhancing students’ English competence through habituation and the language environment at the State Islamic University of Imam Bonjol Padang. The research and development type was used to develop the model in four phases, namely, need analysis, designing the model, validating, and a hypothetical model. 350 randomly selected active students participated in this research. Observation, questionnaires, interviews, and the TOEFL test were used to collect the data. The findings revealed that students' English competence was low, with a mean score of 65. Students tended to develop their competences through listening to music for listening skills, reading articles for reading skills, practicing individually for speaking skills, and sending messages for writing skills, with a mean score of 4.06. Reading, speaking, and writing skills were mostly improving. Students expressed a high demand for English club activities and academic English services to enhance their English competence through habituation and the language environment, with mean satisfaction scores of 84% and 86%. The hypothetical Integrated English Model (IEM) for enhancing English competence through habituation and the language environment consisted of four main phases: planning, organizing, implementing, and evaluating. The study concludes that designing this integrated model is crucial for improving students' English competence at the State Islamic University of Imam Bonjol Padang. It implies that an integrated English model for enhancing English competence will lead to significant improvements in English competence among students.